Structural transformation and electrochemical properties of a nanosized flower-like R-MnO2 cathode in a sodium battery. Issue 1 (14th December 2021) - Qiu, Kai; Zhang, Chao; Yan, Mingxia; Zhao, Shouwang; Fan, Hongwei; An, Shengli; Qiu, Xinping; Jia, Guixiao
Abstract : The difference of Fermi energy level makes the potential plateau of R-MnO2  turn into NaMnO2  lower than that of Na0.33 MnO2  to NaMnO2 . This explains our experimental result from the 1st–2nd voltage capacity profile of R-MnO2  in EC/PC electrolyte. Abstract : High-energy density and low-cost sodium–ion batteries are being sought to meet increasing energy demand. Here, R-MnO2 is chosen as a cathode material of sodium–ion batteries owing to its low cost and high energy density. The structural transformation from the tunnel R-MnO2 to the layered NaMnO2 and electrochemical properties during the charge/discharge are investigated at the atomic level by combining XRD and related electrochemical experiments. Na≤0.04 MnO2 has a tunnel R-MnO2 phase structure, Na≥0.42 MnO2 has a layered NaMnO2 phase structure, and Na0.04−0.42 MnO2 is their mixed phase. Mn 3+ 3d 4 [t2g β3d z 2 (1)3d x 2 − y 2 (0)] in NaMnO2 loses one 3d z 2 electron and the redox couple Mn 3+ /Mn 4+ delivers 206 mA h g −1 during the initial charge. The case that the Fermi energy level difference between R-MnO2 and NaMnO2 is lower than that between the layered Na(12- x )/12 MnO2 and NaMnO2 makes the potential plateau of R-MnO2 turning into NaMnO2 lower than that of the layered Na(12− x )/12 MnO2 to NaMnO2 . This can be confirmed by our experiment from the 1st–2nd voltage capacity profile of R-MnO2 in EC/PC (ethylene carbonate/propylene carbonate) electrolyte. The study would give a new view of the production of sustainable sodium battery cathode materials.